Regional Economic Integration and its Implication on Exports in the Common Market for Eastern and Southern Africa (COMESA) Region (1980e2010) - Mwebaze, Tom; Hisali, Eria; Tumwebaze, Henry (Journal of African Trade, 2024)
One of the major development challenges facing Africa has been the small and fragmented economies with low incomes and low levels of intra-regional trade. To foster economic growth and promote intra-regional exports, Africa has witnessed renewed momentum for regional integration, in particular trade among COMESA countries. The present study employs fixed effects, random effects, and instrumental variables GMM regressions to estimate an augmented trade gravity model. We find that the formation of the COMESA trading bloc has promoted intra-regional exports. This finding suggests that to enhance export flows in the region, the process of economic integration should be deepened.